Physical balance (proportion of concentrates to roughage) in lamb fattening rations. - Cox, R.F. (Kansas Agricultural Experiment Station, 2012)
In several years of experimental studies of physical balance as a factor in determining the value of lamb fattening rations, more than 2000 lambs have been fed, and a wide variety of feeds have been employed. The experimental rations have been made up of feeds ranging from high palatability and nutritive value, such as corn, cottonseed meal, and alfalfa hay, to combinations which have finitely lower nutritive value, particularly the roughages of matured grain varieties of sorghums.
Keywords: Sheep; Concentrates; Roughages; Gain